A coupled hydrodynamic and particle-tracking model for full-process simulation of nonpoint source pollutants. (February 2021) - Jiang, Jinghua; Liang, Qiuhua; Xia, Xilin; Hou, Jingming
Abstract: Nonpoint source (NPS) particulate pollutants are a major source of urban surface pollution. It is essential to better understand and model the dynamic process of NPS pollutants to inform the design of effective strategies for urban stormwater management and pollution control. This work presents a novel coupled hydrodynamic and particle-based model to simulate the full-process dynamics of NPS particulate pollutants from detachment, transport to deposition in urban areas. A particle-based approach is proposed to represent the physical processes of pollutant detachment and deposition. The transport of pollutant particles is simulated using a random-walk particle-tracking model, which can directly trace out the trajectories of individual particles and hence identify the pathways of pollutants. The new coupled hydrodynamic and particle-based stormwater quality model is successfully validated against several analytical and experimental test cases to demonstrate its capability in accurately simulating the full-process dynamics of NPS particulate pollutants in urban areas. Highlights: A new coupled hydrodynamic and particle-based model for urban NPS pollutant dynamics. New particle-based approach for physical representation of pollutant wash-off dynamics. The new model enables direct prediction of trajectories and pathways of pollutants.